CCL5-Mediated Th2 Immune Polarization Promotes Metastasis in Luminal Breast Cancer - Zhang, Qianfei; Qin, Jilong; Zhong, Lin; Gong, Lei; Zhang, Bing; Zhang, Yan; Gao, Wei-Qiang (Cancer research (Chicago, Ill.), 2015)
The tumor-promoting chemokine CCL5 has been implicated in malignant transformation of breast epithelial cells, with studies to date focusing mainly on basal-type breast cancers. In this study, we investigated the consequences of CCL5 deletion in the MMTV-PyMT transgenic mouse model of luminal breast cancer. In this model, primary tumor burden and pulmonary metastases were reduced significantly in CCL5-deficient subjects, an effect found to be associated with a deficit of Th2 (IL4⁺CD4⁺ T) cells. Mechanistic investigations revealed that CCL5 activates CCR3, a highly expressed chemokine receptor on CD4⁺ T cells, and also boosts Gfi1 expression to promote the differentiation of Th2 cells, which enhance the prometastatic activity of tumor-associated myeloid cells. Clinically, polarization toward this immunosuppressive Th2 phenotype was also evident in patients with advanced luminal breast cancer. Thus, our findings showed that CCL5/CCR3 signaling promotes metastasis by inducing Th2 polarization of CD4⁺ T cells, with implications for prognosis and immunotherapy of luminal breast cancer.